The Coordination Function of PT Angkasa Pura II Terminal Inspection Service (TIS) Officers in Fulfilling Standard Service Procedures at Sultan Thaha Syarifuddin Airport, Jambi - Nabila Berliana Defani; Amelia Puspa Tamara (CV. Rayyan Dwi Bharata, 2023)
The coordination function of Terminal Inspection Service (TIS) officers is determined by officers within the organization who have the same goals. Terminal Inspection Service (TIS) officers work with Standard Operating Procedures (SOP) provided by PT Angkasa Pura II, with Standard Operating Procedures (SOP) officers coordinate with other officers so as to achieve optimal work goals. The performance of Terminal Inspection Service officers in a facility maintenance, supervision is very influential on customer satisfaction at the airport. The good condition of the airport terminal will get its own assessment by passengers, the good condition of the airport terminal is of course caused by the coordination of Terminal Inspection Service (TIS) officers. This study used a qualitative research method design, in which data collection was carried out through interviews, observation, documentation, and literature studies in the work area of the Terminal Inspection Service (TIS) officer at Sultan Thaha Syarifuddin Airport, Jambi. This research was conducted to determine the coordination function of the Terminal Inspection Service (TIS) at PT Angkasa Pura II Sultan Thaha Syarifuddin Airport, Jambi. The results of this study are the coordination function of Terminal Inspection Service (TIS) officers, coordination of officers according to SOP, officers resolving obstacles that occur at the airport terminal swiftly and precisely. Terminal Inspection Service (TIS) officers coordinate well between colleagues and superiors in overcoming all existing problems in accordance with Standard Operating Procedures (SOP).